Proceso de Adaptación y Aceptación de las mujeres con diagnóstico de cáncer de cuello uterino del Hospital II - ESSALUD, Tarapoto Enero-Octubre 2014 - Marín Labajos, Hellen (2014)
This study entitled "Process of adaptation and acceptance of women diagnosed With cervical cancer Hospital ESSALUD-Tarapoto II; January-October 2014 "; Quantitative, descriptive simple, prospective cross-sectional study design used Is one box; aimed to identify how the process of adaptation and acceptance Develops over the diagnosis of cervical cancer (cervical cancer), worked with a Population of 30 women with dx of cervical cancer, the instrument gather data Was a questionnaire prepared by the authors who measured the adaptation Process to measure the process of accepting the instrument developed by Avila M. And Canseco C was used; the data was organized based Excel 2013 and SPSS software. V.21. The results found that: 90% of women had an adequate adaptation process Of cervical cancer. According to sub dimensions initial response, dysphoria 23.3% and 21.1% of women have inadequate adaptation to diagnosis of Cervical cancer in sub respectively, and long-term adaptation dimension 27.8% Had adequate adaptation to disease. With regard to acceptance 73.3% of Women favorably accepted the disease. According sub dimensions: denial 63.3%, 56.7% anger, depression, 73.3% of women have an indifferent Acknowledgment against the diagnosis of cervical cancer respectively in the sub Dimensions negotiation, acceptance 60.0% and 100% of women have a. Favorable acceptance disease respectively. In conclusion whether an adequate adjustment to illness will be a favorable Acceptance thereof which will enable women to improve their quality of life i / o Lifestyles.